Association Between Gestational Diabetes Mellitus and Future Risk of Kidney Stones - Mao, Yuanyuan; Hu, Wenbin; Liu, Li; Liu, Qin (Frontiers in Public Health, 2022)
Objective: The association between history of gestational diabetes mellitus (GDM) and risk of kidney stones has not been reported. GDM increases the risk of long-term complications including diabetes, hypertension and metabolic syndrome, which are risk factors of kidney stones. This study aimed to explore the association between previous GDM and odds of kidney stones. Methods: Women (age ≥ 20 years) who had delivered at least one live birth were included from the 2007–2018 National Health and Nutrition Examination Survey cohort (N=12,003). Patients with kidney stones and history of GDM were identified by in-home interview for all participants. Subgroup analyses were conducted by age, race/ethnicity, postpartum duration and status of hypertension, obesity, current diabetes and metabolic syndrome. Results: Previous GDM was positively associated with odds of kidney stones [multivariate-adjusted odds ratio (95% confidence interval): 1.41 (1.13-1.77)], and the association was stronger with odds of passing 2 or more times of kidney stones [1.72 (1.31-2.26)]. In subgroup analyses, the association between previous GDM and odds of kidney stones was significant in women within 15 years of a pregnancy complicated by GDM [1.54 (1.12-2.11)], in obese participants [1.56 (1.18-2.06)], in women without hypertension [1.49 (1.07-2.08)], current diabetes [1.38 (1.02-1.87)] and metabolic syndrome [1.56 (1.10-2.19)], in women of Non-Hispanic White [1.59 (1.15-2.18)] and in women aged more than 50 year [1.45 (1.02-2.07)]. Conclusions: Previous GDM was positively associated with odds of kidney stones, and the association was independent of type 2 diabetes, hypertension and metabolic syndrome.